A copper (II) doped carbon nanotube material and its preparation method and application

The catalytic oxidation of isopropyl hydrogen peroxide by copper (II) doped carbon nanotube material has been solved, and a high-efficiency and environmentally friendly catalytic oxidation reaction is achieved. Improves environmental and biocompatibility of the reaction.

CN113600190BActive Publication Date: 2025-01-07ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111006360.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-30
Publication Date
2025-01-07
Estimated Expiration
2041-08-30

AI Technical Summary

Technical Problem

The current oxidation of isopropyl hydrogen peroxide is low selectivity, and harmful organic solvents and transition metal catalysts are used, which reduces the environmental compatibility and biocompatible of the reaction.

Method used

Using copper (II) doped carbon nanotube material as a catalyst, copper (II) doped carbon nanotube material is prepared by activating and supporting copper (II) salt, and the isopropyl benzene oxide reaction is carried out on the basis of it to achieve Hydrogen peroxide isopropyl benzene isopropyl benzene is prepared with high selectivity.

Benefits of technology

The reaction temperature is significantly reduced, the catalyst usage is reduced, the solvent use is avoided, the conversion rate of isopropyl benzene and the selectivity of isopropyl benzene peroxide isopropyl benzene, and the environmental compatibility and biocompatibility of the reaction are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005059671540000041
    Figure GDA0005059671540000041
Patent Text Reader

Abstract

The present invention relates to a copper (II) doped commercially available carbon nanotube material and a preparation method thereof and its application in catalytic oxidation of cumene compounds to selectively oxidize and prepare cumene hydroperoxide, belonging to the field of organic catalysis and fine organic synthesis. The method comprises: activating carbon nanotubes, dispersing the activated carbon nanotubes in a copper (II) salt aqueous solution of a certain concentration for loading, and heat treating the solid to obtain the copper (II) doped carbon nanotube material. The copper (II) doped carbon nanotube material is applied to a method for catalytic oxidation of cumene compounds to selectively oxidize and prepare cumene hydroperoxide, so that the reaction process does not contain any solvent and auxiliary agent, the catalyst dosage is small, and the cumene conversion rate is high, the cumene hydroperoxide selectivity is high, the by-products are small, and the green development concept of the chemical industry is met. The present invention provides a safe, efficient and feasible method for catalytic oxidation of cumene compounds to synthesize cumene hydroperoxide compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copper (II) doped commercially available carbon nanotube material and a preparation method thereof and application of the material in catalytically oxidizing cumene compounds and selectively oxidizing cumene to prepare cumene hydroperoxide, belonging to the field of organic catalysis and fine organic synthesis. Background Art

[0002] Isopropylbenzene hydroperoxide is an important fine chemical raw material. As a basic raw material, it is widely used in the production of phenol and acetone. It is also an important oxidant in the process of propylene oxidation to prepare propylene oxide. This shows the importance of propylbenzene hydroperoxide synthesis in the chemical industry (ACS Sustainable Chemistry & Engineering 2019, 7: 7708-7715; Chemical Engineering Science 2018, 177: 91-398). The oxidation of propylbenzene to prepare propylbenzene hydroperoxide has also become an important chemical conversion process. At present, the synthesis of propylbenzene hydroperoxide mainly uses propylbenzene as raw material and metal complexes or metal-supported and carbon nanomaterials as catalysts. However, in the current oxidation reaction process, the selectivity of the target product isopropyl hydroperoxide is not high. It is reported that the conversion rate of isopropylbenzene is about 20%, and the selectivity of isopropylbenzene hydroperoxide is 70-85% (Applied Catalysis A, General 2018, 561: 59-67; ChemCatChem 2018, 10: 198-205). In addition, the oxidation process of some isopropylbenzene also uses a large amount of organic solvents and transition metal catalysts that are toxic and harmful to the environment and organisms, which not only reduces the environmental compatibility and biocompatibility of the reaction process, but also causes the product to be contaminated by transition metals (Inorganica Chimica Acta 2019, 486: 425-434; Applied Surface Science 2017, 419: 98-106; Advanced Synthesis & Catalysis 2011, 353: 147-154). Therefore, achieving highly selective oxidation of cumene to prepare cumene hydroperoxide under mild conditions using reagents and catalysts with good environmental and biocompatibility is of great significance in both industrial production and theoretical research, and meets the current society's urgent need for a safe, green, and environmentally friendly chemical industry. Summary of the invention

[0003] In order to overcome the deficiencies of the prior art, the object of the present invention is to provide a copper (II) doped commercially available carbon nanotube material and a preparation method thereof, and its application in the catalytic oxidation of cumene to synthesize cumene hydroperoxide. Carbon nanotubes have a highly developed pore structure, a high specific surface area and a large pore volume, and good chemical stability. These properties make it widely used in electrochemistry, environmental protection, catalysis, etc., especially in the field of catalyst preparation, carbon nanotubes have become an excellent carrier material, which is not only conducive to the dispersion of catalytic active centers, but also has good stability and is suitable for large-scale production applications (ChemCatChem, 2020, (12): 259-266; Green Chemistry, 2020, (22): 742-752). Using carbon nanotubes doped with metallic copper as a catalytic material can not only achieve a high degree of dispersion of copper (II), but also help to improve the stability of copper (II). Applying it to the O2 catalytic oxidation of cumene can not only significantly lower the reaction temperature and reduce the amount of catalyst, but also the oxidation process does not contain any solvents and additives, and has a high selectivity for cumene hydroperoxide. It has the potential to solve the current industrial catalytic oxidation of cumene and its derivatives, such as high reaction temperature, the use of corrosive solvents and additives, low selectivity for cumene hydroperoxide, and easy deep oxidation.

[0004] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0005] One of the purposes of the present invention is to provide a method for preparing a copper (II)-doped carbon nanotube material, the method comprising:

[0006] (1) activating the carbon nanotubes to obtain activated carbon nanotubes;

[0007] (2) dispersing the activated carbon nanotubes in a copper (II) salt aqueous solution of a certain concentration and stirring for a certain period of time to load the carbon nanotubes with copper (II);

[0008] (3) After the loading is completed, the solid is collected, heat-treated under a protective atmosphere, and post-treated to obtain a copper (II)-doped carbon nanotube material.

[0009] Preferably, the diameter of the carbon nanotubes in step (1) is 5 to 15 nm.

[0010] Preferably, in step (1), the carbon nanotubes are dispersed in an aqueous nitric acid solution for activation; more preferably, the activation temperature is 0 to 150° C., more preferably 50 to 100° C.; the activation time is 1.0 to 24.0 h, more preferably 2.0 to 12.0 h.

[0011] Preferably, the concentration of the nitric acid aqueous solution is 1.0 to 14.0 mol / L.

[0012] Preferably, the ratio of the nitric acid aqueous solution to the carbon nanotubes is 5.0-100 mL / g.

[0013] Preferably, in step (1), conventional treatment steps such as filtration and water washing are further included after the activation of the carbon nanotubes.

[0014] Preferably, the copper (II) salt in step (2) is at least one of copper (II) acetate, copper (II) chloride, copper (II) sulfate, and copper (II) nitrate, or a mixture of two or more thereof in any proportion; more preferably, it is one of anhydrous copper (II) acetate and / or its hydrate (such as copper acetate monohydrate), anhydrous copper (II) chloride and / or its hydrate (such as copper chloride dihydrate), anhydrous copper (II) sulfate and / or its hydrate (such as copper sulfate pentahydrate), anhydrous copper (II) nitrate and / or its hydrate (such as copper nitrate trihydrate), or a mixture of two or more thereof in any proportion.

[0015] Preferably, the concentration of the copper (II) salt aqueous solution in step (2) is 0.0010 to 20.0 mol / L.

[0016] Preferably, in step (2), the ratio of the copper (II) salt aqueous solution to the activated carbon nanotubes is 5.0 to 100 mL / g.

[0017] Preferably, the stirring temperature in step (2) is 0 to 200°C, more preferably 50 to 150°C.

[0018] Preferably, the stirring time in step (2) is 1.0 to 24.0 h, more preferably 5.0 to 12.0 h.

[0019] Preferably, after loading in step (3), the solid is collected by filtration and washing, and more preferably, it also includes drying.

[0020] Preferably, the protective atmosphere in step (3) is a mixture of one or more of nitrogen, argon and helium.

[0021] Preferably, the heat treatment temperature in step (3) is 200 to 1000°C, more preferably 400 to 800°C.

[0022] Preferably, the heat treatment time in step (3) is 1.0 to 18.0 h, more preferably 5.0 to 12.0 h.

[0023] Preferably, the post-treatment in step (3) includes conventional steps such as pickling, water washing, and drying.

[0024] Preferably, the pickling is performed by stirring and washing with hydrochloric acid, the concentration of the hydrochloric acid is 0.5 to 10.0 mol / L, more preferably 0.5 to 5.0 mol / L, and the pickling time is 1.0 to 10.0 h.

[0025] Preferably, after the acid washing, the product is filtered and then washed with water until the pH value is 3.0 to 8.0.

[0026] Preferably, the drying is vacuum drying at a temperature of 80°C.

[0027] Preferably, the method is specifically as follows: commercially available carbon nanotubes are dispersed in a certain concentration of nitric acid aqueous solution, stirred at 0-150°C (preferably 50-100°C) for 1.0-24.0h (preferably 2.0-12.0h), and cooled to room temperature. Filtered and washed with water to obtain activated carbon nanotubes. The obtained activated carbon nanotubes are dispersed in a certain concentration of copper (II) salt aqueous solution, stirred and loaded at 0-200°C (preferably 50-150°C) for 1.0-24.0h (preferably 5.0-12.0h), filtered and washed with water. Then, heat treated at 200-1000°C (preferably 400-800°C) under N2 atmosphere for 1.0-18.0h (preferably 5.0-12.0h). Acid washing, water washing, and vacuum drying are performed to obtain copper (II)-doped carbon nanotube material.

[0028] The second object of the present invention is to provide a copper (II) doped carbon nanotube material prepared by the above preparation method.

[0029] The third object of the present invention is to provide a method for preparing cumene hydroperoxide by catalytic oxidation of cumene compounds using the copper (II)-doped carbon nanotube material prepared above.

[0030] Preferably, the application method comprises:

[0031] The copper (II) doped carbon nanotube material is dispersed in the isopropylbenzene compound, the reaction system is sealed, an oxidant is introduced and the temperature is raised to the reaction temperature for stirring reaction, and the isopropylbenzene hydroperoxide compound is obtained after the reaction is completed.

[0032] Preferably, the ratio of the mass (g) of the copper (II) doped carbon nanotubes to the amount (mmol) of the cumene compound is 0.0001%-1% g / mmol.

[0033] Preferably, the reaction temperature is 20-150°C, more preferably 50-100°C.

[0034] Preferably, the reaction pressure is 0.1 to 2.0 MPa, more preferably 0.5 to 1.5 MPa.

[0035] Preferably, the reaction time is 1.0 to 24.0 h, more preferably 2.0 to 10.0 h.

[0036] Preferably, the stirring rate is 200-1200 rpm.

[0037] Preferably, the oxidant is oxygen, air or any mixture thereof.

[0038] Preferably, the application method specifically comprises: dispersing the copper (II) doped carbon nanotube material in cumene, sealing the reaction system, introducing an oxidant at 0.1-2.0 MPa (preferably 0.5-1.5 MPa), stirring and heating to 20-150° C. (preferably 50-100° C.), maintaining the set temperature and pressure, stirring and reacting for 1.0-24.0 h (preferably 2.0-10.0 h), and the reaction solution can be used directly and post-processed. The reaction solution is post-processed to calculate the cumene conversion rate and the cumene hydroperoxide selectivity.

[0039] Preferably, the structural formula of the cumene compound is as shown in formula (I), the structural formula of the corresponding product cumene hydroperoxide compound is as shown in formula (II), and the structural formulas of the by-product acetophenone compound and 2-phenyl-2-propanol compound produced in the oxidation reaction are as shown in formula (III) and (IV), respectively:

[0040]

[0041] Wherein, in formula (I), (II), (III) or (IV), R1, R2, R3, R4 and R5 are each independently: hydrogen, methyl, ethyl, propyl, butyl, isopropyl, tert-butyl, phenyl, 1-naphthyl, 2-naphthyl, methoxy, ethoxy, hydroxyl, mercapto, amino, methylamino, ethylamino, dimethylamino, 1-hydroxyethyl, nitro, cyano, carboxyl, benzyl, fluorine, chlorine, bromine or iodine.

[0042] The method for analyzing the reaction result of the present invention is as follows: after the reaction is finished, the reaction liquid is reduced by triphenylphosphine to generate peroxide, then sampled for analysis, diluted with acetone as a solvent, naphthalene as an internal standard, gas chromatography analysis is performed, and the conversion rate of isopropylbenzene and the selectivity of isopropylbenzene hydroperoxide are calculated.

[0043] The copper (II) doped carbon nanotube material of the present invention is simple to prepare, low in cost and good in thermal stability; the oxidation method does not contain any solvent or auxiliary agent, and the amount of catalyst used is small; under mild conditions, highly selective oxidation of isopropylbenzene is achieved with reagents and catalysts with good environmental compatibility and biocompatibility to prepare isopropyl hydroperoxide, which has important significance in industrial production and theoretical research and meets the urgent needs of society for a green, safe and environmentally friendly chemical industry.

[0044] The beneficial effects of the present invention are mainly reflected in: the method for synthesizing cumene hydroperoxide by catalytic oxidation of cumene by copper (II) doped commercially available carbon nanotube materials has the advantages of low reaction temperature, high cumene conversion rate, high selectivity of cumene hydroperoxide, high safety factor, etc. Therefore, the present invention provides a novel and efficient copper (II) doped carbon nanotube catalyst, and also provides a safe and feasible new method for synthesizing cumene hydroperoxide by catalytic oxidation of cumene. DETAILED DESCRIPTION

[0045] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0046] Examples 1-12 are the synthesis of the copper (II) doped commercially available carbon nanotube material;

[0047] Example 13-45 is the application of the copper (II) doped commercially available carbon nanotube material to catalyze the selective oxidation of cumene compounds to prepare cumene hydroperoxide compounds;

[0048] The carbon nanotubes used in the present invention are commercially available products, the brand is Xianfeng Nano, and the model is XFM061333-86-4. However, it should be known that the same or similar products can be used for the reaction of the present invention; the reagents used are all commercially available analytical grade.

[0049] Example 1

[0050] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 100°C, continued to stir and load for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 4.0h and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -3-100-4-500 (copper acetate, nitric acid solution 3 mol / L, copper loading temperature 100°C, heat treatment 4.0h, heat treatment temperature 500°C).

[0051] Example 2

[0052] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 1mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 100°C, and continued to stir for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 4.0h, and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -1-100-4-500 (copper acetate, nitric acid solution 1 mol / L, copper loading temperature 100°C, heat treatment 4.0h, heat treatment temperature 500°C).

[0053] Example 3

[0054] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 14mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 100°C, continued to stir and load for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 4.0h and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -14-100-4-500 (copper acetate, nitric acid solution 14 mol / L, copper loading temperature 100°C, heat treatment 4.0h, heat treatment temperature 500°C).

[0055] Example 4

[0056] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper chloride aqueous solution, stirred and heated to 100°C, continued to stir and load for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 4.0h and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 氯化铜 -3-100-4-500 (copper chloride, nitric acid solution 3 mol / L, copper load temperature 100°C, heat treatment 4.0h, heat treatment temperature 500°C).

[0057] Example 5

[0058] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper sulfate aqueous solution, stirred and heated to 100°C, and continued to stir for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 4.0h, and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 硫酸铜 -3-100-4-500 (copper sulfate, nitric acid solution 3 mol / L, copper load temperature 100°C, heat treatment 4.0h, heat treatment temperature 500°C).

[0059] Example 6

[0060] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper nitrate aqueous solution, stirred and heated to 100°C, continued to stir and load for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 4.0h and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 硝酸铜 -3-100-4-500 (copper nitrate, nitric acid solution 3 mol / L, copper loading temperature 100°C, heat treatment 4.0h, heat treatment temperature 500°C).

[0061] Example 7

[0062] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 50°C, continued to stir and load for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 4.0h and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -3-50-4-500 (copper acetate, nitric acid solution 3 mol / L, copper loading temperature 50°C, heat treatment 4.0h, heat treatment temperature 500°C).

[0063] Example 8

[0064] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 200°C, and continued to stir for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 4.0h, and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -3-200-4-500 (copper acetate, nitric acid solution 3 mol / L, copper load temperature 200°C, heat treatment 4.0h, heat treatment temperature 500°C).

[0065] Example 9

[0066] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 100°C, and continued to stir for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 200°C under N2 atmosphere, heat treated for 4.0h, and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -3-100-4-200 (copper acetate, nitric acid solution 3 mol / L, copper loading temperature 100°C, heat treatment 4.0h, heat treatment temperature 200°C).

[0067] Example 10

[0068] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 100°C, and continued to stir for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 1000°C under N2 atmosphere, heat treated for 4.0h, and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -3-100-4-1000 (copper acetate, nitric acid solution 3 mol / L, copper load temperature 100°C, heat treatment 4.0h, heat treatment temperature 1000°C).

[0069] Embodiment 11

[0070] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 100°C, and continued to stir for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 1.0h, and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -3-100-1-500 (copper acetate, nitric acid solution 3 mol / L, copper loading temperature 100°C, heat treatment 1.0h, heat treatment temperature 500°C).

[0071] Example 12

[0072] In a 500mL single-mouth round-bottom flask, 5.00g of commercially available carbon nanotubes were dispersed in 250mL of 3mol / L nitric acid aqueous solution, stirred and heated to 80°C, and stirred for 4.0h. Cooled to room temperature, washed with distilled water (3×100mL) to obtain activated carbon nanotubes. In a 250mL single-mouth round-bottom flask, the obtained carbon nanotubes were dispersed in 200mL of 5mol / L copper acetate aqueous solution, stirred and heated to 100°C, continued to stir and load for 12.0h, cooled to room temperature, washed with distilled water (3×100mL), and vacuum dried at 80°C. The obtained material was heated to 500°C under N2 atmosphere, heat treated for 18.0h and then naturally cooled. After cooling to room temperature, 2mol / L hydrochloric acid solution was stirred and washed for 8.0h. Washed with deionized water until neutral, and vacuum dried to obtain copper (II) doped commercial carbon nanotube material C 乙酸铜 -3-100-18-500 (copper acetate, nitric acid solution 3 mol / L, copper loading temperature 100°C, heat treatment 18.0h, heat treatment temperature 500°C).

[0073] Embodiment 13

[0074] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 75%, the selectivity of 2-phenyl-2-propanol was 1.97%, the selectivity of acetophenone was 0.65%, the selectivity of isopropylbenzene hydroperoxide was 97.38%, and the generation of benzoic acid was not detected.

[0075] Embodiment 14

[0076] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 氯化铜-3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 65%, the selectivity of 2-phenyl-2-propanol was 8.67%, the selectivity of acetophenone was 4.62%, the selectivity of isopropylbenzene hydroperoxide was 86.71%, and the generation of benzoic acid was not detected.

[0077] Embodiment 15

[0078] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 硫酸铜 -3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 70.3%, the selectivity of 2-phenyl-2-propanol was 16.37%, the selectivity of acetophenone was 6.95%, the selectivity of isopropylbenzene hydroperoxide was 76.68%, and the generation of benzoic acid was not detected.

[0079] Example 16

[0080] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 硝酸铜-3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 68.4%, the selectivity of 2-phenyl-2-propanol was 10.18%, the selectivity of acetophenone was 3.52%, the selectivity of isopropylbenzene hydroperoxide was 86.30%, and the generation of benzoic acid was not detected.

[0081] Embodiment 17

[0082] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-50-4-5000.0600g was dispersed in 12.0915g (100mmol) cumene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of cumene was 54.7%, the selectivity of 2-phenyl-2-propanol was 10.83%, the selectivity of acetophenone was 19.3%, the selectivity of cumene hydroperoxide was 69.87%, and the generation of benzoic acid was not detected.

[0083] Embodiment 18

[0084] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-1-100-4-5000.0600g was dispersed in 12.0915g (100mmol) cumene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of cumene was 59.8%, the selectivity of 2-phenyl-2-propanol was 6.16%, the selectivity of acetophenone was 6.14%, the selectivity of cumene hydroperoxide was 87.7%, and the generation of benzoic acid was not detected.

[0085] Embodiment 19

[0086] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-10000.0600g was dispersed in 12.0915g (100mmol) cumene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of cumene was 71.6%, the selectivity of 2-phenyl-2-propanol was 4.5%, the selectivity of acetophenone was 4.7%, the selectivity of cumene hydroperoxide was 90.8%, and the generation of benzoic acid was not detected.

[0087] Embodiment 20

[0088] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0050g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The isopropylbenzene conversion rate was 45%, the selectivity of 2-phenyl-2-propanol was 5.12%, the selectivity of acetophenone was 4.37%, the selectivity of isopropylbenzene hydroperoxide was 90.52%, and the generation of benzoic acid was not detected.

[0089] Embodiment 21

[0090] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.120g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80℃ with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80℃ and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 73.8%, the selectivity of 2-phenyl-2-propanol was 6.92%, the selectivity of acetophenone was 5.93%, the selectivity of isopropylbenzene hydroperoxide was 87.15%, and the generation of benzoic acid was not detected.

[0091] Embodiment 22

[0092] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0240g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 58.6%, the selectivity of 2-phenyl-2-propanol was 5.62%, the selectivity of acetophenone was 3.61%, the selectivity of isopropylbenzene hydroperoxide was 90.77%, and the generation of benzoic acid was not detected.

[0093] Embodiment 23

[0094] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) cumene, the reactor was sealed, the temperature was raised to 20°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of cumene was 41.85%, the selectivity of 2-phenyl-2-propanol was 21.6%, the selectivity of acetophenone was 19.99%, the selectivity of cumene hydroperoxide was 58.41%, and the generation of benzoic acid was not detected.

[0095] Embodiment 24

[0096] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 150℃ with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80℃ and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as internal standard. The conversion rate of isopropylbenzene was 70.9%, the selectivity of 2-phenyl-2-propanol was 14.05%, the selectivity of acetophenone was 21.6%, the selectivity of isopropylbenzene hydroperoxide was 64.35%, and the generation of benzoic acid was not detected.

[0097] Embodiment 25

[0098] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 50°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 39.8%, the selectivity of 2-phenyl-2-propanol was 14.38%, the selectivity of acetophenone was 9.72%, the selectivity of isopropylbenzene hydroperoxide was 75.9%, and the generation of benzoic acid was not detected.

[0099] Embodiment 26

[0100] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) cumene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 0.1MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of cumene was 43.5%, the selectivity of 2-phenyl-2-propanol was 13.91%, the selectivity of acetophenone was 14.89%, the selectivity of cumene hydroperoxide was 71.2%, and the generation of benzoic acid was not detected.

[0101] Embodiment 27

[0102] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 2.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 72.6%, the selectivity of 2-phenyl-2-propanol was 12.1%, the selectivity of acetophenone was 2.16%, the selectivity of isopropylbenzene hydroperoxide was 85.74%, and the generation of benzoic acid was not detected.

[0103] Embodiment 28

[0104] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 0.5MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 49.8%, the selectivity of 2-phenyl-2-propanol was 10.2%, the selectivity of acetophenone was 23.7%, the selectivity of isopropylbenzene hydroperoxide was 66.1%, and the generation of benzoic acid was not detected.

[0105] Embodiment 29

[0106] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) cumene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 200rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of cumene was 69.85%, the selectivity of 2-phenyl-2-propanol was 12.79%, the selectivity of acetophenone was 8.9%, the selectivity of cumene hydroperoxide was 78.31%, and the generation of benzoic acid was not detected.

[0107] Embodiment 30

[0108] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 1000rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 73%, the selectivity of 2-phenyl-2-propanol was 6.03%, the selectivity of acetophenone was 9.81%, the selectivity of isopropylbenzene hydroperoxide was 84.16%, and the generation of benzoic acid was not detected.

[0109] Embodiment 31

[0110] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80℃ with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80℃ and 400rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 72.6%, the selectivity of 2-phenyl-2-propanol was 5.95%, the selectivity of acetophenone was 9.75%, the selectivity of isopropylbenzene hydroperoxide was 84.3%, and the generation of benzoic acid was not detected.

[0111] Embodiment 32

[0112] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 1.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The isopropylbenzene conversion rate was 38.6, the selectivity of 2-phenyl-2-propanol was 20.34%, the selectivity of acetophenone was 15.27%, the selectivity of isopropylbenzene hydroperoxide was 64.39%, and the generation of benzoic acid was not detected.

[0113] Embodiment 33

[0114] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) cumene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 12.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of cumene was 71.6%, the selectivity of 2-phenyl-2-propanol was 19.6%, the selectivity of acetophenone was 3.1%, the selectivity of cumene hydroperoxide was 77.3%, and the generation of benzoic acid was not detected.

[0115] Embodiment 34

[0116] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 12.0915g (100mmol) isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 16.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of isopropylbenzene was 73.4%, the selectivity of 2-phenyl-2-propanol was 7.73%, the selectivity of acetophenone was 7.37%, the selectivity of isopropylbenzene hydroperoxide was 84.9%, and the generation of benzoic acid was not detected.

[0117] Embodiment 35

[0118] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 13.4g (100mmol) 4-methylisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 4-methylisopropylbenzene was 57%, the selectivity of 2-phenyl-2-propanol was 10.72%, the selectivity of acetophenone was 8.28%, the selectivity of hydroperoxide isopropylbenzene was 81%, and the generation of benzoic acid was not detected.

[0119] Embodiment 36

[0120] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 15.0g (100mmol) 2-methoxyisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 2-methoxyisopropylbenzene was 38%, the selectivity of 2-phenyl-2-propanol was 5%, the selectivity of acetophenone was 6%, the selectivity of hydroperoxide isopropylbenzene was 89%, and the generation of benzoic acid was not detected.

[0121] Embodiment 37

[0122] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 16.50g (100mmol) 4-nitroisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 4-nitroisopropylbenzene was 66%, the selectivity of 2-phenyl-2-propanol was 6.1%, the selectivity of acetophenone was 11.2%, the selectivity of hydroperoxide isopropylbenzene was 82.7%, and the generation of benzoic acid was not detected.

[0123] Embodiment 38

[0124] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 16.40g (100mmol) 4-carboxyisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 4-carboxyisopropylbenzene was 57%, the selectivity of 2-phenyl-2-propanol was 3.89%, the selectivity of acetophenone was 4.11%, the selectivity of hydroperoxide isopropylbenzene was 92%, and the generation of benzoic acid was not detected.

[0125] Embodiment 39

[0126] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 16.20g (100mmol) 4-isopropyl isopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 4-isopropyl isopropylbenzene was 62%, the selectivity of 2-phenyl-2-propanol was 3%, the selectivity of acetophenone was 7%, the selectivity of hydroperoxide isopropylbenzene was 63.8%, and the generation of benzoic acid was not detected.

[0127] Embodiment 40

[0128] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 13.50g (100mmol) 3-aminoisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 3-aminoisopropylbenzene was 92%, the selectivity of 2-phenyl-2-propanol was 28%, the selectivity of acetophenone was 7.37%, the selectivity of hydroperoxide isopropylbenzene was 0%, and the generation of benzoic acid was not detected.

[0129] Embodiment 41

[0130] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 13.50g (100mmol) 4-aminoisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 4-aminoisopropylbenzene was 70%, the selectivity of 2-phenyl-2-propanol was 25%, the selectivity of acetophenone was 4%, the selectivity of hydroperoxide isopropylbenzene was 0%, and the generation of benzoic acid was not detected.

[0131] Embodiment 42

[0132] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 19.60g (100mmol) 4-phenylisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 4-phenylisopropylbenzene was 31%, the selectivity of 2-phenyl-2-propanol was 5%, the selectivity of acetophenone was 3.85%, the selectivity of hydroperoxide isopropylbenzene was 91.15%, and the generation of benzoic acid was not detected.

[0133] Embodiment 43

[0134] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 13.60g (100mmol) 3-hydroxyisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 3-hydroxyisopropylbenzene was 83%, the selectivity of 2-phenyl-2-propanol was 11%, the selectivity of acetophenone was 0%, the selectivity of hydroperoxide isopropylbenzene was 0%, and the generation of benzoic acid was not detected.

[0135] Embodiment 44

[0136] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜-3-100-4-5000.0600g was dispersed in 13.60g (100mmol) 4-hydroxyisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 4-hydroxyisopropylbenzene was 86%, the selectivity of 2-phenyl-2-propanol was 0%, the selectivity of acetophenone was 0%, the selectivity of hydroperoxide isopropylbenzene was 16%, and the generation of benzoic acid was not detected.

[0137] Embodiment 45

[0138] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, C 乙酸铜 -3-100-4-5000.0600g was dispersed in 14.90g (100mmol) 4-methylaminoisopropylbenzene, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.0MPa. The reaction was stirred at 80°C and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 13.1150g (50.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with naphthalene as the internal standard. The conversion rate of 4-methylaminoisopropylbenzene was 71%, the selectivity of 2-phenyl-2-propanol was 12%, the selectivity of acetophenone was 8.1%, the selectivity of hydroperoxide isopropylbenzene was 34%, and the generation of benzoic acid was not detected.

Claims

1. A method for synthesizing cumene hydroperoxide compounds by catalytic oxidation of cumene compounds by copper (II) doped carbon nanotube materials, characterized in that: The method comprises: dispersing a copper (II)-doped carbon nanotube material in an isopropylbenzene compound, sealing the reaction system, introducing an oxidant, heating the system to a reaction temperature, stirring the system, and obtaining an isopropylbenzene hydroperoxide compound after the reaction is completed; the isopropylbenzene compound comprises one of isopropylbenzene, 4-methylisopropylbenzene, 4-isopropylisopropylbenzene, 2-methoxyisopropylbenzene, 4-nitroisopropylbenzene, 4-carboxyisopropylbenzene, 4-phenylisopropylbenzene, 4-hydroxyisopropylbenzene, and 4-methylaminoisopropylbenzene; The preparation method of the copper (II) doped carbon nanotube material is as follows: (1) activating the carbon nanotubes to obtain activated carbon nanotubes; (2) dispersing the activated carbon nanotubes in a copper (II) salt aqueous solution of a certain concentration and stirring to load copper (II); (3) After the loading is completed, the solid is collected, heat-treated under a protective atmosphere, and post-treated to obtain a copper (II)-doped carbon nanotube material.

2. The method for synthesizing cumene hydroperoxide compounds by catalytic oxidation of cumene compounds by copper (II) doped carbon nanotube materials as claimed in claim 1, characterized in that: In the step (1), the carbon nanotubes are dispersed in a nitric acid aqueous solution for activation.

3. The method for synthesizing cumene hydroperoxide compounds by catalytic oxidation of cumene compounds by copper (II) doped carbon nanotube materials as claimed in claim 2, characterized in that: The concentration of the nitric acid aqueous solution is 1.0-14.0 mol / L; the ratio of the nitric acid aqueous solution to the carbon nanotubes is 5.0-100 mL / g.

4. The method for synthesizing cumene hydroperoxide compounds by catalytic oxidation of cumene compounds by copper (II) doped carbon nanotube materials as claimed in claim 1, characterized in that: The copper (II) salt in step (2) is one or a mixture of any proportion of copper acetate, copper chloride, copper sulfate and copper nitrate.

5. The method for synthesizing cumene hydroperoxide compounds by catalytic oxidation of cumene compounds by copper (II) doped carbon nanotube materials as claimed in claim 1, characterized in that: The concentration of the copper (II) salt aqueous solution in step (2) is 0.0010-20.0 mol / L; the ratio of the copper (II) salt aqueous solution to the activated carbon nanotubes is 5.0-100 mL / g.

6. The method for synthesizing cumene hydroperoxide compounds by catalytic oxidation of cumene compounds by copper (II) doped carbon nanotube materials as claimed in claim 1, characterized in that: In the step (3), the heat treatment temperature is 200 to 1000° C., and the heat treatment time is 1.0 to 18.0 h.

7. The method for synthesizing cumene hydroperoxide compounds by catalytic oxidation of cumene compounds by copper (II) doped carbon nanotube materials as claimed in claim 1, characterized in that: The mass ratio of the copper (II) doped carbon nanotubes to the amount of cumene compounds is 0.0001%-1% g / mmol; the reaction temperature is 20-150° C., the reaction pressure is 0.1-2.0 MPa, and the reaction time is 1.0-24.0 h.

8. The method for synthesizing cumene hydroperoxide compounds by catalytic oxidation of cumene compounds by copper (II) doped carbon nanotube materials as claimed in claim 1, characterized in that: The oxidant is oxygen, air or a mixture of the two in any proportion.